Analisis Hermeneutika Yuridis Pasal 239 Ayat (2) Huruf D dan G Undang-Undang No.17 Tahun 2014 - Utari, Anak Agung Adik Sri; Rumiartha, I Nyoman Prabu Buana (Sahabat Publikasi, 2024)
Article 239 paragraph (1) and paragraph (2) of the MD3 Law regulates the right of political parties to conduct inter-term dismissal (PAW) of DPR members. However, the ambiguity in Article 239 paragraph (2) letters d and g caused controversy because the terms of PAW became unclear and often misused to resolve internal party conflicts. This study aims to analyze the juridical hermeneutics of the provisions of Article 239 paragraph (2) letter d and g of Law Number 17 of 1014 concerning MPR, DPR, DPD, and DPRD. The results showed that abstract interpretations of the phrases